Pengaruh Lingkungan Kerja Dan Disiplin Kerja Terhadap Produktivitas Karyawan Pada PT. Sari Asri Tani - Akbar, Muhamad; Akbar, M. Azis Firdaus; Kusumah, Anuraga (CV. ITTC INDONESIA, 2023)
This study aims to determine the effect of work environment and work discipline on employee productivity at PT. Sari Asri Tani. This type of research is quantitative. The population of this study are employees of PT. Sari Asri Tani. The analysis used is a quantitative technique using a saturated sampling technique with a total population of 30 respondents. The research instrument is a questionnaire. The results of the research instrument test used multiple regression analysis tests, t tests, and f tests. The results of the analysis show that the work environment and work discipline have a significant effect on employee productivity with multiple regression analysis test results of Y = 6.427 + 0.509 X1 + 0.331 X2. The work environment t test results obtained tcount > ttable 4.315 > 1.703 meaning that Ho1 is rejected, and Ha1 is accepted, work discipline t test results are 8.427 > 1.703 meaning Ho2 is rejected and Ha2 is accepted, and the f test results are 12.859 > 3.34 meaning Ho3 is rejected and Ha3 is accepted. Based on the results of these data it can be concluded that the work environment and work discipline affect the productivity of employees at PT. Sari Asri Tani.